Artificial Intelligence-Assisted Loop Mediated Isothermal Amplification(AI-LAMP) for Rapid Detection of SARS-CoV-2 - Rohaim, M.A.; Clayton, E.; Sahin, I.; Julianne, V.; Khalifa, M.E.; Al-Natour, M.Q.; Bayoumi, M.; Poirier, M.C.; Branavan, M.; Mukunthan, T.; Chaudhry, N.S.; Ravinder, S.; et al. (MDPI, 2020)
Untilvaccinesandeffectivetherapeuticsbecomeavailable,thepracticalsolutiontotransit safelyoutofthecurrentcoronavirusdisease19(CoVID-19)lockdownmayincludetheimplementation ofaneffectivetesting,tracingandtrackingsystem.However,thisrequiresareliableandclinically validateddiagnosticplatformforthesensitiveandspecificidentificationofSARS-CoV-2.Here, wereportonthedevelopmentofadenovo,high-resolutionandcomparativegenomicsguided reverse-transcribedloop-mediatedisothermalamplification(LAMP)assay.Tofurtherenhancethe assayperformanceandtoremoveanysubjectivityassociatedwithoperatorinterpretationofresults, weengineeredanovelhand-heldsmartdiagnosticdevice.Therobustdiagnosticdevicewasfurther furnishedwithautomatedimageacquisitionandprocessingalgorithmsandthecollateddatawas processedthroughartificialintelligence(AI)pipelinestofurtherreducetheassayruntimeandthe subjectivityofthecolorimetricLAMPdetection.ThisadvancedAIalgorithm-implementedLAMP (ai-LAMP)assay,targetingtheRNA-dependentRNApolymerasegene,showedhighanalytical sensitivityandspecificityforSARS-CoV-2.Atotalof~200coronavirusdisease(CoVID-19)-suspected NHSpatientsamplesweretestedusingtheplatformanditwasshowntobereliable,highlyspecific andsignificantlymoresensitivethanthecurrentgoldstandardqRT-PCR.Therefore,thissystemcould provideanefficientandcost-effectiveplatformtodetectSARS-CoV-2inresource-limitedlaboratories.
Keywords: SARS-CoV-2; Diagnosis; LAMP; Point of care; Artificial intelligence